Water injection in spark ignition engines—Impact on engine cycle - Michael Fratita; Florin Popescu; Jorge Martins; F.P. Brito; Tiago Costa; Ion Ion (Energy Reports, 2021)
Water injection in internal combustion engines is mainly used for additional cooling of the combustion chamber and knock suppression. The main advantages of the water injection are the potential for the enhancement of the performance of the engine. Studies conducted so far have aimed to track engine performance at maximum load and fuel consumption (brake-specific fuel consumption BSFC). Specialized literature is less consistent as regards to the injection of water at medium and low loads. This work monitors the effects of water injection at medium loads and the evolution processes of the four-strokes in the engine with and without water injection. A side-valve, air cooled natural aspirated engine with water and fuel injections in the intake manifold was used for this study. The work during expansion was increased, but this trend was reversed by the higher loads required during intake, compression and exhaust strokes, leading to a reduction in the indicated efficiency when water was injected.